Casts, splints, and support bandages nonoperative treatment and perioperative protection - Dresing, Klaus 1952-; Trafton, Peter G. (Peter Grier) 1943- (AOtrauma, 2014)
Casts, Splints, and Support Bandages: Nonoperative Treatment and Perioperative Protection provides an extensive overview of the history, principles, methods, and techniques for applying a modern plaster or synthetic cast